Effectiveness of Social Work-based Emotional Intelligence Training Programs in Schools (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The purpose of this study was to investigate the extent to which emotional intelligence (EI) training programs that were administered by social workers successfully assisted students in integrating themselves socially and academically, as well as in developing their emotional competencies. Through the use of a quasi-experimental pre-post methodology, the study was carried out with the participation of two groups of students from different schools. In order to enhance their emotional intelligence, the experimental group participated in a program that lasted for ten days and consisted of sessions that lasted between an hour and an hour and a half. Only pre- and post-tests were completed by the members of the control group. The findings of the ANCOVA test demonstrated that the students' levels of emotional intelligence had significantly increased as a consequence of their participation in the EI training program. It is important to note that the improvements in academic and social adjustment did not reach the level of statistical significance. Furthermore, in compared to their younger colleagues, older participants and female students did considerably better on all dependent variables; yet, there was no statistically significant difference between the sexes when it came to academic and social adjustment. Educational institutions may be able to assist students in better integrating their academic and social lives by using emotional intelligence training programs that have been designed by social workers, according to research.